ASIS&T: The student perspective. Issue 5 (19th June 2014) - Dumas, Catherine; Rorissa, Abebe
Abstract: EDITOR'S SUMMARY An engaged student membership is a key source of strength and vitality for a professional organization like ASIS&T. With 43 student chapters around the world, ASIS&T has a good foundation of student support; having an active chapter at each university with studies in information science would further strengthen the Association. An early 2014 survey elicited responses from 38 current or past students, 28 of whom had a local ASIS&T student chapter with 23 being members. Just over half had attended an ASIS&T Annual Meeting. Respondents noted the value of networking within the Association and special interest groups and the assistance available for career and research goals. They also observed drawbacks including the cost of Annual Meeting attendance and feeling lost at the large conference. Students are drawn by the opportunities for involvement and networking. Among the numerous suggestions offered to strengthen and enrich the student experience were leadership training, practical skill development and improved communications.